A-146 Parent Responses on the Behavior Rating Inventory of Executive Function-2 Are more Reflective of Child Cognitive Functioning than Teacher Responses. (30th August 2021) - Larson, Kera; Wilbur, Jessica; Hamilton, Elizabeth
Abstract: Objective: The Behavior Rating Inventory of Executive Function, Second Edition (BRIEF-2) is widely used to assess executive processes in children and adolescents. The BRIEF-2 manual (2015) indicates small correlations between executive functioning and intellectual performance on the Wechsler Intelligence Scales for Children, Fourth Edition, but no studies have evaluated the BRIEF-2 and the Woodcock Johnson Tests of Cognitive Abilities, Fourth Edition (WJ-IV-Cog). The current study examined whether parent and teacher BRIEF-2 responses were linked to WJ-IV-Cog indices in a rural school-based sample. Method: A sample of (n = 18) students attending rural school districts was extracted from an archival dataset. Participants (age range 7–17, M = 12.9, SD = 2.5) included 15 males and 3 females, who were referred for psychoeducational assessment. Results: Correlational analyses indicated a moderate relationship between the BRIEF-2 parent Global Executive Composite (GEC) and the WJ-IV-Cog domains of comprehension-knowledge (Gc), fluid reasoning (Gf), and auditory processing (Ga) (p < 0.05). Subsequent analyses of the three BRIEF-2 indices showed that the Parent Behavioral Regulation Index (BRI) was related to both Gc and Gf (p < 0.05), while the Parent Cognitive Regulation Index (CRI) was significantly associated with Gc, Gf, and Ga (p < 0.05). Teacher ratings of GEC, BRI, and CRI were independent from child intellectual performance. However, Teacher Emotion Regulation Index (ERI) was moderately related with GIA (p < 0.05). Conclusion: Current findings support a moderate relationship between parent ratings on the BRIEF-2 and specific cognitive domains on the WJ-IV-Cog. Results should be interpreted within the context of both a small sample size and the designation of subjects for psycho-educational assessment evaluations.